Population pharmacokinetics of imipenem in critically ill patients with suspected ventilator‐associated pneumonia and evaluation of dosage regimens - Couffignal, Camille; Pajot, Olivier; Laouénan, Cédric; Burdet, Charles; Foucrier, Arnaud; Wolff, Michel; Armand‐Lefevre, Laurence; Mentré, France; Massias, Laurent (British journal of clinical pharmacology, 2014)
Aims Significant alterations in the pharmacokinetics (PK) of antimicrobials have been reported in critically ill patients. We describe PK parameters of imipenem in intensive care unit (ICU) patients with suspected ventilator‐associated pneumonia and evaluate several dosage regimens. Methods This French multicentre, prospective, open‐label study was conducted in ICU patients with a presumptive diagnosis of ventilator‐associated pneumonia caused by Gram‐negative bacilli, who empirically received imipenem intravenously every 8 h. Plasma imipenem concentrations were measured during the fourth imipenem infusion using six samples (trough, 0.5, 1, 2, 5 and 8 h). Data were analysed with a population approach using the stochastic approximation expectation maximization algorithm in Monolix 4.2. A Monte Carlo simulation was performed to evaluate the following six dosage regimens: 500, 750 or 1000 mg with administration every 6 or 8 h. The pharmacodynamic target was defined as the probability of achieving a fractional time above the minimal inhibitory concentration (MIC) of >40%. Results Fifty‐one patients were included in the PK analysis. Imipenem concentration data were best described by a two‐compartment model with three covariates (creatinine clearance, total bodyweight and serum albumin). Estimated clearance (between‐subject variability) was 13.2 l h−1 (38%) and estimated central volume 20.4 l (31%). At an MIC of 4 μg ml−1, the probability of achieving 40% fractional time > MIC was 91.8% for 0.5 h infusions of 750 mg every 6 h, 86.0% for 1000 mg every 8 h and 96.9% for 1000 mg every 6 h. Conclusions This population PK model accurately estimated imipenem concentrations in ICU patients. The simulation showed that for these patients, the best dosage regimen of imipenem is 750 mg every 6 h and not 1000 mg every 8 h.